Associations of vitamin D status with all-cause and cause-specific mortality in long-term prescription opioid users - Dai, Shan; Wu, Junpeng; Wang, Peng; Hu, Zhenhua (Frontiers in Nutrition, 2024)
Objective This study aimed to investigate the association between serum 25-hydroxyvitamin D (25(OH)D) concentrations and mortality in long-term prescription opioid users. Methods The study included 1856 long-term prescription opioid users from the National Health and Nutrition Examination Survey (NHANES, 2001–2018). Mortality status were determined by matching with the National Death Index (NDI) records until December 31, 2019. Multivariable Cox proportional hazard models were constructed to assess the association. Results Over a median follow-up period of 7.75 years, there were 443 cases of all-cause mortality, including 135 cardiovascular disease (CVD) deaths and 94 cancer deaths. After multivariable adjustment, participants with serum 25(OH)D concentrations within 50.00 to <75.00 nmol/L and ≥ 75 nmol/L had a lower risk of all-cause mortality, with hazard ratios (HRs) of 0.50 (95% confidence interval [CI] 0.29, 0.86) and 0.54 (95% CI 0.32, 0.90), respectively. Nevertheless, no significant association was found between serum 25(OH)D concentrations and the risk of CVD or cancer mortality. The RCS analysis revealed a non-linear association of serum 25(OH)D concentration with all-cause mortality (p for non-linear = 0.01). Per 1-unit increment in those with serum 25(OH)D concentrations <62.17 nmol/L corresponded to a 2% reduction in the risk of all-cause mortality (95% CI 0.97, 1.00), but not changed significantly when 25(OH)D concentrations ≥62.17 nmol/L. Conclusion In conclusion, a non-linear association existed between serum 25(OH)D concentrations and all-cause mortality in long-term prescription opioid users. Maintaining serum 25(OH)D concentrations ≥62.17 nmol/L may be beneficial in preventing all-cause mortality in this population.